A Cross-sectional Study to Assess the Effect of COVID-19 Stressors and Knowledge on Infection Control Measure on Nurse’s Performance at a Selected Hospital at Sirsa Haryana - Linil, M. (Indian Journal of Nursing Sciences, 2024)
Background: The SARS-CoV-2 virus, which causes the coronavirus disease (COVID-19), was initially discovered in Wuhan, China, in December 2019. A current study purpose was to evaluate how COVID-19 stresses affected nurses’ performance during the epidemic. Methods: A total of 30 nurses were selected through convenient sampling technique; 18 were female nurses and 12 were males. A descriptive cross-sectional research design has been utilized to evaluate the COVID-19 stressors effect on nurses. The data were collected with selfstructured questionnaire to measure the knowledge and infection control measures on COVID-19 and COVID-19 stress scale to measure the varied stress levels among nurses. Results: 70.0% of the studied participants had a satisfactory level of knowledge and infection control measures and 30.0% had good knowledge. 60.0% of the nurses who took part in the study reported moderate psychological stress levels on the COVID-19. Nurses’ adequate degree of knowledge and COVID-19 psychological stressor levels are significantly correlated. Conclusion: The majority of nurses possessed satisfactory knowledge and infection control measures. The majority of them had moderate amounts of COVID-19 psychological stress.